2008
DOI: 10.1530/eje-08-0097
|View full text |Cite
|
Sign up to set email alerts
|

Incretin levels in polycystic ovary syndrome

Abstract: Objective: Polycystic ovary syndrome (PCOS) has been linked to a high risk of type 2 diabetes mellitus. Disturbances in the secretion of the incretin hormones glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) have been observed in states with impaired glucose regulation. This paper considers the secretion of GIP and GLP-1 after oral glucose load in a group of lean, glucose-tolerant PCOS women in comparison with age-and body mass index (BMI)-matched healthy women. Design: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
3
58
0
9
Order By: Relevance
“…This is partly in accordance with the findings of Vrbikova et al [30]. They found significantly higher levels of GIP, but significantly lower levels of GLP-1, in the late phases of the OGTT in PCOS compared with controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is partly in accordance with the findings of Vrbikova et al [30]. They found significantly higher levels of GIP, but significantly lower levels of GLP-1, in the late phases of the OGTT in PCOS compared with controls.…”
Section: Discussionsupporting
confidence: 92%
“…Few previous studies have addressed the incretin effect in women with PCOS. In a recent study, Vrbikova et al [30] described higher levels of GIP in women with PCOS. The GLP-1 responses were identical in women with and without PCOS in the early phases of an OGTT, but lower levels were found in the late phases of the test [30].…”
Section: Introductionmentioning
confidence: 94%
“…Lower active GLP1 levels have been observed in patients with insulinresistant states, such as type 2 diabetes mellitus, PCOS, and lean PCOS (27,28). GLP1 receptor agonists and analogues improve glucose homeostasis and reduce body weight.…”
Section: Glucagon-like Peptide 1 Receptor Agonists and Analoguesmentioning
confidence: 99%
“…61 The 63,64 Recent studies have demonstrated lower GIP levels in obese women with PCOS. 65,66 Given that insulin resistance is of pathophysiological relevance to the endocrine and metabolic dysfunction of PCOS, the therapeutic benefit of incretin therapy in this population is plausible. …”
Section: Thiazolidinedionesmentioning
confidence: 99%